Bank of terms the special language of nursing of a school hospital - Maria Miriam Lima da Nóbrega; Telma Ribeiro Garcia; Ana Claudia Torres de Medeiros; Gabriela Lisieux Lima de Souza (Rev Rene)
This is a descriptive study developed with the aim of unifying the research developed in the clinics of the University Hospital Lauro Wanderley-UFPB, aiming to build a Bank of Terms the Special Language of Nursing. To serve the purpose of the study there was the identifi cation as well as the evaluation of all the terms of the particular language of nursing, the mapping of terms identifi ed in clinics with those in the International Classifi cation for Nursing Practice (ICNP®) Version 1.0, and the compilation of defi nitions of the terms contained in the classifi cation of these axes, which formed the Bank of Terms of the Special Language of Nursing. It is believed that it is necessary to continue this study to examine the terms that are not listed in CIPE® and is made the validation of all the terms contained in the bank of terms, so that its use is allowed in the development of affi rmative diagnoses/outcomes and nursing interventions.